Lycopene: Prospects for chemoprevention and treatment of prostate cancer - Heath, Elisabeth; Şahin, Kazım; Seren, Soley; Küçük, Ömer (My University, 2006)
Lycopene is a carotenoid compound found in certain fruit, such as tomato, watermelon, pink grapefruit and guava in high concentrations. Dietary intake of lycopene is inversely associated with the risk of prostate cancer (Pca). Preclinical studies show that lycopene has potent in vitro and in vivo anti-tumour effects on Pca cells suggesting potential preventive and therapeutic roles for this phytochemical. However, the small number and size of clinical trials conducted with lycopene preclude firm conclusions with regard to its use in Pca prevention and treatment in humans. Further research, including hypothesis-driven mechanistic studies as well as larger randomized clinical intervention trials with lycopene in Pca patients, are warranted. © CABI Publishing 2006.
Keywords: Lycopene; Nutrition; Prevention; Prostate cancer; Treatment